(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article aims to provide a thorough exploration of the clinical-anatomical foundation underlying surgical interventions for posterior mediastinitis. By examining relevant literature, we elucidate the current understanding of the anatomical structures involved, explore various surgical methods employed, and discuss the outcomes and implications of these interventions.